Prostaglandin E2 synthesis and secretion the role of PGE2 synthases - Park, Jean Y (Clinical immunology (Orlando, Fla.), 2006)
Prostaglandin E2 (PGE2) is a principal mediator of inflammation in diseases such as rheumatoid arthritis and osteoarthritis. Nonsteroidal anti-inflammatory medications (NSAIDs) and selective cyclooxygenase-2 (COX-2) inhibitors reduce PGE2 production to diminish the inflammation seen in these diseases, but have toxicities that may include both gastrointestinal bleeding and prothrombotic tendencies. In cells, arachidonic acid is transformed into PGE2 via cyclooxygenase (COX) enzymes and terminal prostaglandin E synthases (PGES). Accumulating data suggest that the interaction of various enzymes in the PGE2 synthetic pathway is complex and tightly regulated. In this review, we summarize the synthesis and secretion of PGE2. In particular, we focus on the three isoforms of the terminal PGES, and discuss the potential of targeting PGES as a more precise strategy for inhibiting PGE2 production